Rethinking training in food policy analysis: how relevant is it to policy reforms? - Babu, Suresh Chandra (International Food Policy Research Institute, 1996)
This view point aims at providing some pointers for those involved in food and agricultural policy analysis training in order to generate amongst them a dialogue that may result in improved training programs. The relevance of currently offered training courses to economic policy reforms is discussed. The constraints and challenges faced by the organizers of training courses in redesigning training courses to meet the constantly changing policy environment in developing countries are presented. It is argued that there is a need for rethinking methods of training in food and agricultural policy analysis in meeting the changing needs of policy decisionmaking in developing countries.